2011
DOI: 10.1016/j.jpurol.2011.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of nephrolithiasis in otherwise healthy versus medically complex gastrostomy fed children

Abstract: Stone disease in GSF is multifactorial, and half of our study group had an identifiable risk factor for nephrolithiasis. A recurring pattern of alkaline urine and calcium phosphate stone formation was evident. GSF did not have higher rates of hypercalciuria despite chronic immobilization and markedly lower bone density. An awareness of the potential risk factors identified is mandatory for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Our findings expand upon clinical details regarding GTF patients with stones and help to answer some of the questions posed by Smith et al 7 Akin to patients in their investigation, we found a high proportion of calcium phosphate stones, supporting a metabolic explanation for the increased risk of stones in GTF children. Smith et al 7 reported similar rates of hypercalciuria in GTF patients with stones, and otherwise healthy children with stones, and suggest that hypercalcemia due to immobility was not a key factor in stone promotion. Similarly, we found no association between mobility status and urolithiasis in GTF children with and without stones.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings expand upon clinical details regarding GTF patients with stones and help to answer some of the questions posed by Smith et al 7 Akin to patients in their investigation, we found a high proportion of calcium phosphate stones, supporting a metabolic explanation for the increased risk of stones in GTF children. Smith et al 7 reported similar rates of hypercalciuria in GTF patients with stones, and otherwise healthy children with stones, and suggest that hypercalcemia due to immobility was not a key factor in stone promotion. Similarly, we found no association between mobility status and urolithiasis in GTF children with and without stones.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings expand upon clinical details regarding GTF patients with stones and help to answer some of the questions posed by Smith et al 7 Akin to patients in their investigation, we found a high proportion of calcium phosphate stones, supporting a metabolic explanation for the increased risk of stones in GTF children. Smith et al 7 reported similar rates of hypercalciuria in GTF patients with stones, and otherwise healthy children with stones, and suggest that hypercalcemia due to immobility was not a key factor in stone promotion.…”
Section: Discussionsupporting
confidence: 85%
“…Smith et al 7 reported similar rates of hypercalciuria in GTF patients with stones, and otherwise healthy children with stones, and suggest that hypercalcemia due to immobility was not a key factor in stone promotion. Similarly, we found no association between mobility status and urolithiasis in GTF children with and without stones.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have suggested that a low urine volume and dehydration are risk factors for stone formation with TPM. 10,18 Although we had no data on the water balance in our cohort, we also speculate that the volume of water intake is a distinguishing factor in our TPM-treated children. This study has several limitations, including its retrospective nature, small number of patients, and lack of urinary chemistry data for the non-TPM-treatment patients.…”
Section: Discussionmentioning
confidence: 87%
“…16,17 Smith et al stated that neither immobility nor hypercalciuria in and of themselves are major risk factors in the nephrolithiasis seen in gastrostomy-fed stone-formers, of whom 94% were immobile. 18 Bladder stasis from immobility and neurogenic bladder and metabolic factors predisposing to hypercalciuria are risk factors for stone formation in nonambulatory children treated with TPM. 10 We also speculate that the same pathophysiology underlies our TPM-treatment group.…”
Section: Discussionmentioning
confidence: 99%